Structurer, affirmer son identité : stratégies identitaires des fans LGBT de l’Eurovision au cours de la pandémie de Covid-19 - Oranie Abbes (Genre, Sexualité et Société)
The Eurovision Song Contest is subject to virulent criticism from the artistic and intellectual elites. Yet, the defense of individual and collective rights of minorities appears to be a particularly sensitive issue. Commonly (re)named with religious terms such as “gay Pesach” or “gay Christmas”, this event is considered as a “structuring experience” of the identity of individuals claiming a different sexual orientation or gender. Recently, the contest has been challenged by the Covid-19 pandemic. This article highlights the networking strategies established by LGBT fans of the ESC, in order to structure an identity-based community, as they were unable to attend the contest “in real life”. Firstly, I highlight these fans form a subaltern counterpublic that seizes the contest in order to assert a certain number of claims in favor of sexual minorities. Secondly, I analyze the ways in which this counterpublic organized itself online and developed new communal strategies during the pandemic. Finally, I emphasize that this new organization tends to maintain and even strengthen inequalities amongst the ESC LGBT fan community.